Screening and Isolation of Marine Actinomycetes from Visakhapatnam Sea Coast Showing Antagonistic Activity Against Selective Human Pathogenic Mirocroorganisms - Gopi Reddy, N.; Ramakrishna, D.P.N.; Patnaik, Shamistha; Siva Kumar†, K.; Rama Rao, M.; Raja Gopal, S.V. (Asian Journal of Chemistry, 2010)
Twenty seven marine actinomycetes species were isolated from Visakhapatnam Sea Coast of Bay of Bengal and were screened for their antagonistic activity against 4 pathogenic fungal species and 7 pathogenic bacterial species. Among all the isolate No. 10 Streptomyces rochei (MTCC 10109) showed antagonizing effect against all pathogenic organisms studied and the antagonistic activity is very high against Candida tropicana and Staphylococcus aureus.